GOOD GOVERNANCE OF KOPERASI WANITA SERBA USAHA “SETIA BUDI WANITA” JAWA TIMUR - Devy Sylvia Puspitasari; Unti Ludigdo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This research was conducted to understand the implementation of good governance on Koperasi Wanita Serba Usaha “Setia Budi Wanita” Jawa Timur. Cooperative is economic organization that based on sense of family. Women’s Cooperative in the present society with the purpose to achieve the welfare of members and society with profesionalism, independent woman, qualified and integrity. This type of research is a qualitative descriptive method. Instruments used in data collection are interviews, observation, and documentation. The results of the research represent passage of the good governance principles includes of transparency in the provisioning information for administrators, employees, PPL, PJ, members in a transparent and opened, so that every employee already knows how the system that are within the cooperative principle accountibility. While, the principle of responsibility shown SBW towards employees by providing a range of benefits, health insurance, safety and social responsibility to the society. Then the principle of independency showed nothing intervention from the internal, but external side there is a little ideological and philosophical differences cooperative. Finally, the Fairness principle, shareholders (members) receive equal and fair treatment in the implementation of the RAT and the division SHU, stakeholders of the employees who were recruited based on their expertise, so the company does not discriminate against employees based on racial and establish a system of reward and punishment is fair. Key Word : Cooperative, Good Governance